Rural Finance in Nigeria : Integrating New Approaches - World Bank (Washington, DC, 2012)
The rural space is home to 53 percent of Nigeria's population and more than 70 percent of its poor. While it is well understood in Nigeria that financial exclusion of the rural population stunts development, still fewer than 2 percent of rural households have access to any sort of institutional finance. Access to financial services is a key ingredient to rural development: it increases incomes through productive investment, helps create employment opportunities, facilitates investments in health and education, and reduces the vulnerability of the poor by helping them to smooth their income patterns over time. A lack of rural access to financial services not only retards rural economic growth, but also increases poverty and inequality. While Nigeria's own long history with rural finance shows a clear appreciation for the importance of rural access, the persistent absence of sustainable access yields important lessons for the future.